The topic of the warrior woman in ’El conde Partinuplés’ by Ana Caro de Mallén - Clavijo Corchero, Álvaro (Huarte de San Juan. Filología y Didáctica de la Lengua, 2025)
In this paper, the paradigms of the warrior woman in the palatine comedy El conde Partinuplés (1653) by Baroque playwright Ana Caro de Mallén (1590-1649) are studied. To do this, it will be essential to review not only the social formation of women in the 17th century, but also the constitution of the model of the warrior woman in the theatre of the time. After that, the study will focus on the construction of the female protagonists of this theatrical piece, women completely opposed to the sociocultural paradigm of the time. In this way, it will be shown that Rosaura and Lisbella are clear references to this literacy topic, who exhibit great strength and independence. Likewise, it can be seen that both distance themselves from the social conventions of women in the 17th century